Classification and Genesis of Late Paleozoic, Volcanic Rocks from Peshawar Plain, North West Pakistan - Rafiq, Mohammad; Shah, Amir; Hamidullah, Syed; Sayab, Mohammad (Journal of Himalayan Earth Sciences, 1997)
Acidic microporphyries and rhyolites of Late Paleozoic age are intimately associated with acidic plutonic rocks, i.e., the Ambela granitic complex of alkaline igneous province of Peshawar plain. Basic rocks occurring as flows are also associated with these acidic rocks. Field evidences including the association of metasedimentary sequence of Carboniferous age, i.e., Jaffar Kandao and Baroach Formation, provide constraints on the date of their emplacement. The microporphyries and rhyolites have a fine-grained texture with feldspars and quartz as phenocrysts. The rocks are classified as A-type, mildly alkaline and peraluminous on the basis of major and minor element chemistry. Tectono-magmatic discrimination diagrams, Zr and Ta concentration, Hf/Th and Hf/Ta ratios, and low Sr reveals that these rocks are of crustal origin and were emplaced in intra-cratonic rift environment. The Th, U and Ta concentrations indicate crustal contamination, and Eu anomaly shows soda metasomatism due to the intrusion of late magmatic fluids in these rocks.